“On the books” yet “off the record”-occupational injury and migrant women: scoping review findings from OECD countries, with implications for New Zealand - Radka, Kelly; Wyeth, Emma H.; Craik, Brooke; Ergler, Christina R.; Derrett, Sarah (Frontiers in Global Women's Health, 2024)
Introduction Little appears to be known regarding the work-related injury (WRI) experiences of migrants (those born in a country other than their identified host country) and specifically, women migrants. Methods As part of a wider PhD project investigating the WRI experiences of New Zealand (NZ) migrants, a review of NZ mainstream media coverage of migrants WRIs was undertaken, which identified no representations of migrant women's WRI experiences. In turn, a scoping review was undertaken to identify peer-reviewed publications reporting empirical findings about WRI experiences and outcomes for migrants in Organization for Economic Co-operation and Development (OECD) member countries, including NZ. This paper aims to identify and describe findings for migrant women specifically. From 2,243 potential publications, 383 proceeded to full text review; ultimately 67 were retained. These 67 publications were reviewed to identify findings specifically for occupationally injured migrant women; 22 such publications (from 21 studies) were found. This paper reports: the characteristics of identified studies; characteristics of migrant women within; frameworks and theories used, and knowledge (and gaps) related to occupationally injured migrant women. Results Publications came from only four OECD countries, the United States, Canada, Australia, and Spain. A range of study designs, and topic areas (working conditions, legal rights, identities, the role of gatekeepers, and precarity), were identified; however, only three studies reported findings for longer-term experiences and outcomes of WRIs. Nine publications considered theoretical models underpinning research, including theories about precarious work, stigmatization, and citizenship. However, there was a paucity of analyses of the WRI experience throughout the life-course, highlighting a gap in understanding of how these experiences are “lived” over the long term by occupationally injured migrant women. Discussion Scoping review findings were synthesized using a provisional “matryoshka framing narrative” model, to be refined through forthcoming qualitative interviews with occupationally injured NZ migrant women. This model highlights the multitude of influences in WRI experiences, potentially specific to migrant women, suggesting the consequences of WRIs may be uneven, with migrant women experiencing different, and potentially, greater disparities in outcomes. These findings provide an impetus to investigate knowledge gaps and urgently address potential disparities in WRI outcomes for migrant women specifically.